Optimal Timing of Antiretroviral Therapy Initiation in Children and Adolescents With Human Immunodeficiency Virus-Associated Pulmonary Tuberculosis. (13th September 2022) - Kay, Alexander; Mendez-Reyes, Jose; Devezin, Tara; Bakaya, Meenakshi; Steffy, Teresa; Dlamini, Sandile; Msekandiana, Amos; Ness, Tara; Bacha, Jason; Amuge, Pauline; Matshaba, Mogomotsi; Chodota, Moses; et al.
Abstract: Background: There is insufficient evidence in children and adolescents with human immunodeficiency virus (CAHIV) to guide the timing of antiretroviral treatment (ART) initiation after starting treatment for pulmonary tuberculosis (pTB). To address this knowledge gap, we evaluated the risk of mortality associated with timing of ART initiation in ART-naive CAHIV treated for pTB. Methods: Data were extracted from electronic medical records of ART-naive patients, aged 0–19 years, who were treated for HIV-associated pTB at Baylor Centers of Excellence in Botswana, Eswatini, Malawi, Lesotho, Tanzania, or Uganda between 2013 and 2020. Data were analyzed against a primary outcome of all-cause mortality with unadjusted Kaplan-Meier curves and Cox proportional hazard models. Results: The study population included 774 CAHIV with variable intervals to ART initiation after starting TB treatment: <2 weeks (n = 266), 2 weeks to 2 months (n = 398), >2 months (n = 66), and no ART initiated (n = 44). Adjusted Cox proportional hazards models demonstrated increased mortality 1 year from TB treatment initiation in children never starting ART (adjusted HR [aHR]: 2.67; 95% CI: 1.03, 6.94) versus children initiating ART between 2 weeks and 2 months from TB treatment initiation. Mortality risk did not differ for the <2-weeks group (aHR: 1.02; 95% CI: .55, 1.89) versus the group initiating ART between 2 weeks and 2 months. Conclusions: This retrospective study demonstrated no increase in mortality among CAHIV initiating ART <2 weeks from TB treatment initiation. Given the broad health benefits of ART, this evidence supports the recent WHO recommendation for CAHIV to initiate ART within 2 weeks of initiating TB treatment. Abstract : This retrospective study evaluates mortality risk in ART-naive children and adolescents categorized by the timing of ART initiation following tuberculosis (TB) treatment initiation. Our analysis demonstrates no increased mortality when starting ART within 2 weeks of TB treatment initiation.